PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERMEDIA DAN PENGETAHUAN AWAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Zulyadaini . (Universitas Batanghari Jambi, 2017)
ABSTRACT: The aims of this research is to know influence the instructional model and knowledge early to learning outcomes. Research method is quasi-experimental disign with treatmen by level 2 X 2. Data was collected with learning outcomes test. The result of this research shows that: in total learning outcomes of students who use STAD cooperative learning model were higher than those who use conventional model. in total learning outcomes of students on the higher knowledge early were higher than those lower knowledge early. The students with higher knowledge early achieved higher learning outcomes by using STAD cooperative learning modelas same as used conventional model. The students with lower knowledge early achieved learning outcomes by using STAD cooperative learning modelapproach as same as used conventional model. There were several not interaction effects between the instructional model with knowledge early toward the students’ learning outcomes.Keywords :Instructional Model, Contextual Teaching And Learning (CTL) Approach, Perseption, Learning Outcomes